Microplastics as a sedimentary component in reef systems: A case study from the Java Sea. Issue 6 (12th June 2021) - Utami, Dwi Amanda; Reuning, Lars; Konechnaya, Olga; Schwarzbauer, Jan
Abstract: Microplastic pollution has been reported from coral reef systems all over the tropics. Exposure to microplastics has several negative impacts on coral health, such as bleaching, tissue necrosis, or an impairment of the coral's immune system. Despite this potential risk for reef systems, the controlling processes for microplastics dispersion and accumulation in reef sediments are still largely under‐studied. Presented here is a study of microplastics (125 µm to 5 mm) distribution in two tropic atoll reef platforms in Kepulauan Seribu, Indonesia. Sediment samples were collected in different facies zones within the reef platform. Microplastics were concentrated using density floatation and characterized by light and scanning electron microscopy. Some particles were identified as polypropylene using micro‐Fourier transform infrared spectroscopy. All recovered microplastics were classified as secondary microplastics, likely derived from marine and local sources, with fibres as the most abundant type. Microplastics are showing similar transport and accumulation behaviour as fine siliciclastic grains. The abundance of microplastic is controlled by the proximity to the source area of larger plastic debris and hydrodynamic processes. Microplastics are not only present in low energy environments but also high energy settings such as the reef crest. Processes that contribute to accumulation in reef sediments are biofouling, interlocking and the creation of compound grains. Microplastics are present in sediment close to the seafloor (0 to 3.5 cm) but also at depths between 3.5 cm and 7.0 cm. Microplastic particles from below 3.5 cm are unlikely to be remobilized under modal weather conditions in the studied equatorial reefs. Subtidal reef sediment therefore can be regarded as a permanent sink for microplastics. The study shows that microplastics in coral reef environments deserve careful consideration since microplastics pose an additional threat to corals and their ability as framework builders in reef systems.